EFEK PEMBERIAN MATRIX METALLOPROTEINASE-9 ( MMP- 9) RNA INTERFERENCE TERHADAP EKSPRESI MMP- 9 PADA KULTUR SEL ENDOTEL VASKULAR - Wulandari, Lely Retno; Suyuti, Hidayat; Dewi, Nadia Artha; Refa, Safaruddin (Jurnal Kedokteran Brawijaya, 2006)
ABSTRACT Retinal neovascularization is the main problem that causes blindness in many types of eye desease. Neovascularization occurs in ischemic retina, and several important mediators that induce neovascularization is secreted by the surrounding cell and endothelial cell vessels. Matrix metalloproteinase-9 is an enzyme secreted by endothelial cell vessels and plays an important role in the pathogenesis of retinal induce neovascularization. Vascular endothelial cells were cultured and transfected with Matrix Metalloproteinase -9 RNA interference in two doses (100nM or 200nM) and the cells were taken at 24,  48  and  72  hours.  The  expression  of  Matrix  Metalloproteinase  -9  protein  levels  were  examined  by immunocytochemistry, and compared with control group. The data were analyzed with factorial anova. Statistical analysis showed that transfection with different doses of MMP-9 RNAi gave a significant different effect on MMP-9 expression (p-value < 0.05), while exposure time did not give significant difference (p-value < 0.05). This in-vitro study indicated that transfection  of  MMP-9  RNAi  with  dose  200nM  reduced the  expression  of  MMP-9  by  50%  compared  to  the  control. Because exposure time was not significant, the lowest expression of MMP-9 can be achieved by transfecting MMP-9 RNAi 200nM for 24 hours. This is the first study that demonstrates the effectiveness of RNA interference mediated targeting  of MMP-9 to reduce the MMP-9 expression in vascular endothelial cell lines Key Words  : Matrix Metalloproteinase -9 - RNA interference - vascular endothelial cell lines.